Conformance contrast testing between rates of pulmonary tuberculosis in Ecuadorian border areas - Claudia Ortiz-Rico; Cristina Aldaz; Héctor Javier Sánchez-Pérez; Miguel Martín Mateo; Natalia Romero-Sandoval (Instituto Nacional de Salud Pública, 2015)
Objective. To estimate rates of cases of respiratory symptomatic subjects and the incidence rate of pulmonary tuberculosis in two border areas of Ecuador, and contrast them with official figures. Materials and methods. Cross-sectional survey in the southeastern (SEBA), and the Andean southern Ecuadorian border areas (ASBA), which were conducted, respectively, in 1 598 and 2 419 persons aged over 15 years recruited over periods of three weeks. In identified respiratory symptomatic cases, a sputum sample was taken for smear testing. The results (odds ratios and their respective 95% confidence intervals), were compared with local and national official figures using maximum likelihood contrasts. Results. The rates of respiratory symptomatic subjects (7.7% and 5.9% in the SEBA, and ASBA, respectively) and of pulmonary tuberculosis (cumulative incidence rates of 125 and 140 per 100 000 inhabitants, in the same order) were significantly greater than the official figures (of 0.98 and 0.99% for respiratory symptomatic subjects in the SEBA and ASBA, respectively; and of 38.23 per 100 000 inhabitants for pulmonary tuberculosis in Ecuador as a whole) (p<0.001). Conclusion. It is necessary to reinforce both active case finding for respiratory symptomatic subject cases, and epidemiological surveillance of pulmonary tuberculosis in Ecuadorian border regions.